PENGINTEGRASIAN TEKNOLOGI DIGITAL AI TERHADAP KEMAMPUAN LITERASI NUMERASI SEKOLAH DASAR - innah, Mutmainnah; Nurhayana , Nurhayana; Ni’ma Wati, Ni’ma Wati; Ainun Taswirai, Ainun Taswirai; Istiqamah, Istiqamah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low numeracy literacy levels among elementary school students in Indonesia and the need for AI-based adaptive learning innovations. The research aims to comprehensively examine implementation strategies, effectiveness, and systemic challenges regarding the integration of Artificial Intelligence (AI) digital technology to enhance students' numeracy literacy at the elementary school level. A Systematic Literature Review (SLR) methodology was employed, comprising planning, conducting, and reporting phases. A search for scholarly articles was conducted across databases such as Google Scholar, DOAJ, ResearchGate, and Sinta for the period 2020–2026, yielding 25 key reference articles that met the inclusion criteria. The findings indicate that AI technology is integrated through learning chatbots, interactive media, digital gamification, adaptive modules, and intelligent tutoring systems. Implementation strategies predominantly combine AI with active learning models, such as Project-Based Learning (PjBL), Problem-Based Learning (PBL), and differentiated instruction. Analysis results consistently demonstrate that AI-based tools have a significant positive impact on improving learning outcomes, conceptual understanding, problem-solving skills, and student motivation. However, implementation still faces obstacles, including limited technological infrastructure, varying levels of teacher digital competence, and the risk of reduced student social interaction. The study concludes that integrating AI technology can support personalized and adaptive mathematics learning processes, thereby strengthening children's numeracy literacy.